Non-financial reporting and company financial performance: a systematic literature review and integrated framework - Crous, Cornelie; Battisti, Enrico; Leonidou, Erasmia (My University, 2021)
Purpose: The purpose of this paper is to examine the different aspects of non-financial reporting that may influence company financial performance. In particular, the authors present an integrated framework of these features that have a direct impact on the financial sustainability of firms for future researchers to further explore and expand the boundaries of the domain. Design/methodology/approach: A systematic literature review of peer-reviewed papers, covering the period 2015–2020, was done, and 41 paper were identified and analysed via a thematic review, to identify variables that either positively or negatively impact on the financial performance of listed companies. The literature focuses on disclosures related to integrated reporting disclosures, sustainability disclosures (also called corporate social responsibility (CSR) disclosures) and corporate governance disclosures. A synthesised inter-textual coherence strategy has been followed during the interpretation of the findings. Findings: The results of the synthesised inter-textual coherence strategy were the development of an integrated framework, which indicates that the inclusion of control variables in regression analysis has no impact on the direction of the relationship between quality reporting and financial reporting. Originality/value: To the best of the authors’ knowledge, this paper is the first to provide a comparison between the impact of the different types of reporting and financial sustainability.
Keywords: Company financial performance; Financial sustainability; Integrated framework; Non-financial reporting; Systematic literature review